On the use of presage detectors for the dosimetry of helical tomotherapy small fields. (September 2016) - Moutsatsos, A.; Pantelis, E.; Antypas, C.; Petrokokkinos, L.; Pappas, E.P.; Zoros, E.; Pantelakos, P.; Georgiou, E.; Karaiskos, P.
Abstract : Introduction: The use of small fields in modern radiotherapy techniques has stretched the importance of verifying the delivered 3D dose distributions characterized by steep dose gradients and complex shapes. In the absence of an ideal dosimeter a multi-detector approach is essential. Purpose: To apply 3D PRESAGE dosimetry for the verification of helical TomoTherapy dose distributions and assess possible corrections of the A1SL ion-chamber response for a head-and-neck plan. Materials and methods: A plan-class specific reference field ( f pcsr ), as recommended by TG-148, and a typical head-and-neck irradiation plan were delivered to a PMMA phantom incorporating appropriate inserts for A1SL ion-chamber, film and PRESAGE dosimeters. Irradiation of f pcsr permitted the evaluation of the corresponding k( Q pcsr, f pcsr ; Q ref, f ref ) correction factor for the A1SL chamber, through comparison to PRESAGE measurements. PRESAGE dosimetry results for the head-and-neck plan, were compared to TPS calculations and corresponding measurements from 1D/2D dosimeters commonly employed for TomoTherapy QA purposes. Results: Although within experimental uncertainties A1SL chamber was found to overestimate the dose at f pcsr by almost 2%, in agreement with published results using alanine dosimeters. Agreement within uncertainties was also observed between planned and presage-measured dose distribution for the head-and-neck plan, exhibiting local gamma index passing rates >90%. When placed within a homogeneous dose distribution, the response of A1SL seemed to be correction free. Conclusion: Besides water equivalence and exquisite spatial resolution, necessitated for small field dosimetry and determination of appropriate correction factors, PRESAGE dosimeters offer the advantage of 3D dose verification. Disclosure: Research supported by an IKY fellowship of excellence for postdoctoral research in Greece–Siemens Program.